Italian Sociology,1945-2010 : An Intellectual and Institutional Profile - Cossu, Andrea; Bortolini, Matteo (Palgrave Macmillan UK : Imprint: Palgrave Pivot, 2017)
This book provides a comprehensive profile of the development of sociology in Italy from the post-war period to the present day. The first English-language account of the history of Italian sociology, it focuses on the process of institutionalization of the discipline within the Italian university system and its changing relationships with extra-academic actors and institutions: political parties, unions, the Catholic Church, political and social movements, as well as local and national governments. Arranged chronologically across eight chapters, it presents all major steps in the development of the discipline in a theoretically-informed but accessible way. The authors explore the pioneering phase of the 1950s to the establishment of the first academic chairs in the 1960s, from the student revolts of 1968 to the creation of the first sociological association in the 1980s and up to the present day. It will appeal to social science and history scholars and students, as well as readers interested in the history of Contemporary Italy.
Keywords: Social sciences.; Italy -- History.; Cultural studies.; Sociology.; Historical sociology.; elektronické knihy; electronic books